2012
DOI: 10.1186/1475-2891-11-69
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ramadan fasting on cardiovascular risk factors: a prospective observational study

Abstract: BackgroundPrevious research has shown that Ramadan fasting has beneficial effects on cardiovascular risk factors, however there are controversies. In the present study, the effect of Ramadan fasting on cardiovascular risk factors has been investigated.MethodThis is a prospective observational study that was carried out in a group of patients with at least one cardiovascular risk factor (including history of documented previous history of either coronary artery disease (CAD), metabolic syndrome or cerebro-vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
134
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(151 citation statements)
references
References 30 publications
11
134
3
3
Order By: Relevance
“…The HDL-C level was significantly increased in ARF comparison to that of BRF. This findings are similar with some other researchers 11,13 . In contrast, some investigators found significant increased levels of serum TC and LDL in healthy subjects at the end of Ramadan.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The HDL-C level was significantly increased in ARF comparison to that of BRF. This findings are similar with some other researchers 11,13 . In contrast, some investigators found significant increased levels of serum TC and LDL in healthy subjects at the end of Ramadan.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, some investigators observed that mean serum TC and LDL-C levels were significantly decreased whereas, HDL-C was significantly increased 11,13 . In contrast, some other researchers found significant increased levels of serum TC and LDL-C with significant decreased level of HDL-C in healthy subjects at the end of Ramadan.…”
Section: Received June 2015;mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are not in agreement with several studies. 2 In fact, during Ramadan, not only the eating pattern is altered but also the amount and type of food consumed. Foods that are rich in fat and protein, or that contain large quantities of carbohydrate, are selectively consumed in Ramadan.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, little is known about the effect of Ramadan fasting on hemostatic profile particularly in patients with cardiovascular disease (CVD) risks who are exposed to hypercoagulable states. The majority of these patients including those with stable coronary artery diseases are particularly vulnerable to the modification of the coagulation pattern.…”
Section: Introductionmentioning
confidence: 99%